The Chemical Quality of Tuna (Thunnus albacares) Nugget with Addition Purple Cabbage (Brassica oleracea) Flour: MUTU KIMIA NUGGET IKAN TUNA (Thunnus albacares) DENGAN PENAMBAHAN TEPUNG KUBIS UNGU (Brassica oleracea) - Astri Iga Siska (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
Tuna fish nuggets (Thunnus albacares) are easily oxidized so that the addition of purple cabbage flour (Brassica oleracea) is expected to improve the chemical quality of these fish nuggets. The purpose of this study was to determine the effect of adding purple cabbage flour on the chemical quality of tuna fish nuggets so as to produce tuna fish nuggets with the best quality. The research method used experimental methods and was designed using a factorial randomized block design with two factors, namely the concentration of purple cabbage flour (0%, 0.7%, 1.4%, 2.1%, and 2.8%) and storage time (0 days and 3 days). Parameters observed were water content, ash content, fat content, protein content, peroxide value and thiobarbituric acid (TBA). Parameter data were analyzed by analysis of variance at 5% significance level using SPSS 22 software and if there was a significant difference, further Tukey test was carried out. The results showed that the addition of purple cabbage flour concentration had a significant effect on the parameters of protein content, peroxide number and TBA, and the storage time had significantly affect the parameters of protein content, fat content, peroxide number and TBA.The chemical quality of the selected tuna fish nuggets was in the treatment of adding 1,4% concentration of cabbage flour without storage.